Analysis Regulation Accountability of Hajj Fund Governance - Siti Nuridah; Rony Marthin Sitohang; Tasrip Tasrip; Muammar Taufiqi Lutfi Mustofa; Muhammad Naufal Majid (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Hajj fund governance is an important aspect in maintaining the integrity and transparency of Hajj fund management. This research aims to examine regulations governing accountability in the governance of Hajj funds using the literature study method. This article involves a review of various literature sources such as journals, books, and related publications. In this study, various regulations will be revealed that have been implemented to increase accountability in the governance of Hajj funds. Apart from that, this research will also highlight the challenges and opportunities faced in accountability of these regulations. The results of this research explain that regulations governing accountability in the governance of Hajj funds have been implemented in Indonesia. These regulations include laws, regulations of the minister of religion, and decisions of the minister of religion which aim to increase transparency and accountability in the management of Hajj funds as well as regulatory accountability in the governance of Hajj funds facing challenges, including effective supervision, risk management, sustainability and regulatory updates, as well as active role of related institutions. It is hoped that it can provide a better understanding of the accountability regulations for Hajj fund management and its contribution to improving the management of Hajj funds.